ANALISIS MANAJEMEN PENGELOLAAN DANA ZAKAT DAN POTENSI ZAKAT DIBAZNAS KABUPATEN SAROLANGUN - Sindy Febriyanti; Febriyanti, Sindy; Rafidah, Rafidah (Manajemen Keuangan Syariah, 2025)
This study aims to explain how the Analysis of Zakat Fund Management and Zakat Potential at Baznas Sarolangun Regency. This study uses a qualitative approach with a descriptive method type, namely a problem that guides researchers to explore the situation to be studied thoroughly. Data collection techniques with field research, while the tools used are observation, interviews and documentation. The data analysis used is descriptive qualitative analysis. The results of this study inform that the management at BAZNAS Sarolangun Regency is good although in terms of collection there are still many things that need to be improved again so that the results of the collected zakat potential can be maximized according to the targets that have been set.